City Branding Festival Budaya Isen Mulang Sebagai Komunikasi Pariwisata - Ni Nyoman Ayu Wilantari; Helena Jovaka Puja Ananda (Tampung Penyang, 2023)
Cultural festivals are actually one of the cultural preservation activities that are communicated to the wider community through various media. Festivals are an important means of communication to build, empower and recognize a cultural identity. Therefore, as a means of communication, it is appropriate for a festival event to be planned through a communication strategic planning process so that it can run effectively. The Isen Mulang Cultural Festival (FBIM), is included in the type of Festival High profile general celebration of the arts, because it is an event that has been arranged in a clear agenda, which is held every year in May to celebrate the Anniversary of the Central Kalimantan Provision. City branding is a city marketing strategy with the aim of strengthening relationships and building a good image of the city with visitors. Tourism communication is a human activity in conveying information about travel to an area or tourist object that will be visited by tourists while enjoying the journey from one tourist attraction to another, so that tourists are interested and arrive at an action to visit.